Klasifikasi Penerimaan Beras Miskin (RASKIN) Menggunakan Metode K-Nearest Neighbor - Mukti Ali Mohammad; Asmaul Husnah Nasrullah; Rofiq Harun (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2023)
Rice is the staple food of most of Indonesia's population. Rice for the poor is a staple food subsidy in the form of rice intended for poor families as an effort from the government to improve food security and provide protection to poor families. Therefore, in 2002 the Indonesian government launched the rice for the poor program as an implementation of the government's consistency. The rice for the poor program is stipulated in the Presidential Regulation of the Republic of Indonesia No. 15 of 2010 on the Acceleration of Poverty Reduction and Presidential Instruction No. 3 of 2010 on Equitable Development Programs. This program aims to reduce the expenditure burden of target households by meeting some of their basic needs in the form of rice. In addition, the program, rice for the poor, aims to increase and open access to family food through the sale of rice to beneficiary families with a predetermined amount. One of the efforts to overcome these problems is to implement one of the methods in data mining, namely classification, which can group data more accurately following the level of similarity of the data characteristics. In this research, data mining analysis is carried out with classification techniques using the K-Nearest Neighbor method. The variables applied in this study are government, education, income, housing conditions, employment, and government assistance card holders